A low end-tidal CO2/arterial CO2 ratio during cardiopulmonary resuscitation suggests pulmonary embolism. (December 2018) - Aagaard, Rasmus; Løfgren, Bo; Caap, Philip; Mygind-Klausen, Troels; Bøtker, Morten T.; Granfeldt, Asger
Abstract: Introduction: Identifying reversible causes of cardiac arrest is challenging. The diagnosis of pulmonary embolism is often missed. Pulmonary embolism increases alveolar dead space resulting in low end-tidal CO2 (EtCO2 ) relative to arterial CO2 (PaCO2 ) tension. Thus, a low EtCO2 /PaCO2 ratio during resuscitation may be a sign of pulmonary embolism. Methods: Post hoc analysis of data from two porcine studies comparing ultrasonographic measurements of right ventricular diameter during resuscitation from cardiac arrest of different causes. Pigs were grouped according to cause of arrest (pulmonary embolism, hypovolemia, primary arrhythmia, hypoxia, or hyperkalaemia) and EtCO2 /PaCO2 ratios were compared. Results: Data from 54 pigs were analysed. EtCO2 levels at the third rhythm analysis were significantly lower when cardiac arrest was caused by pulmonary embolism than by primary arrhythmia, hypoxia and hyperkalaemia, but there was no significant difference between pulmonary embolism and hypovolemia. In contrast, PaCO2 levels were higher in cardiac arrest caused by pulmonary embolism than in the other causes of cardiac arrest. Consequently, the EtCO2 /PaCO2 ratio was lower in pulmonary embolism 0.2 (95%CI 0.1–0.4), than in hypovolaemia 0.5 (95%CI 0.3–0.6), primary arrhythmia 0.7 (95%CI 0.7–0.8), hypoxia 0.5 (95%CI 0.4–0.6), and hyperkalaemia 0.6 (95%CI 0.6–0.7). Conclusion: A low EtCO2 /PaCO2 ratio during cardiopulmonary resuscitation suggests pulmonary embolism.